Using social media for smoking cessation interventions: a systematic review. (January 2021) - Luo, T; Li, MS; Williams, D; Phillippi, S; Yu, Q; Kantrow, S; Kao, YH; Celestin, M; Lin, WT; Tseng, TS
Background: Previous studies have shown that smoking tobacco significantly increases both incidence and mortality rates for many diseases. Social media has become one of the most influential platforms for various smoking cessation interventions. However, results from smoking cessation interventions have differed from study to study. Limited studies have summarised cessation outcomes from social media–based interventions. Therefore, the objective of this review is to explore the effectiveness of using social media for smoking cessation. Methods: We searched PubMed, MEDLINE, PsycINFO, and CINAHL for articles between June 2008 and June 2018, and also assessed the references of selected articles. We included studies that used social media as intervention platforms, provided a baseline assessment before the intervention, and provided smoking cessation outcomes after the intervention. Results: We identified 13 original studies that enrolled between 16 and 1698 participants; 7-day Point Prevalence Abstinence (PPA) rate was the most frequently used measure of abstinence, with a range of 7%–75%, regardless of the measurement time, study design, and analysis methods. Social media–based smoking cessation interventions were effective, because (1) smokers reported higher 7-day PPA rates after intervention compared to baseline and (2) smokers reported higher 7-day PPA rates in intervention groups than in control groups. Moreover, at each time point, approximately half of all smokers in studies reporting abstinence were found to be biochemically abstinent. There were no significant differences in the effectiveness of smoking cessation outcomes between those that used existing popular social networking platforms (e.g. Pechmann et al 's studies) and those that used individually designed interactive platforms (e.g. MyLastDip, iQuit system, Quitxt system). Conclusions: This review highlights the effectiveness of social media–based smoking cessation intervention studies. Due to the widespread use of social media, as well as its low cost, we suggest embedding smoking cessation interventions within existing popular social media platforms.